PENGARUH BANTUAN SOSIAL DAN PEMBERDAYAAN MASYARAKAT MELALUI USAHA MIKRO KECIL MENENGAH TERHADAP PENGENTASAN KEMISKINAN DI KOTA PAREPARE - Ridha, Muh Rasyid; Sinring, Bahar; Baharuddin, Dahlia (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to: (1) To find out the effect of social assistance on poverty alleviation in parepare city; (2) To know the influence of community empowerment through small and medium micro enterprises on poverty alleviation in parepare city; (3) To find out how much influence social assistance and community empowerment through small and medium micro enterprises to poverty alleviation in parepare city. This study uses primary and secondary data. Based on the problem formulation and research hypothesis that has been described earlier, it appears that the relationship between the variables that are the focus of this study as a whole shows complex and tiered casual relationships. This relationship involves dependent variables i.e. poverty alleviation; independent variables i.e. social assistance and community empowerment through small and medium-sized micro enterprises. The results showed that: 1) social assistance has no partial significant effect on poverty alleviation in parepare city 2) community empowerment has a partial significant effect on poverty alleviation in parepare city 3) social assistance and community empowerment through small and medium micro enterprises provide determination of influence contribution of 68% to poverty alleviation in parepare city